EFFECTIVENESS OF HYBRID GROUP GUIDANCE WITH COGNITIVE RESTRUCTURING TECHNIQUES TO OVERCOME THE PROBLEM OF NATIONAL COMMITMENT - Virera, Dinda Rossa Aldyan; Zamroni, Edris; Hidayati, Richma (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
The Society 5.0 era brings a big challenge for Indonesia to maintain the nation's identity in the midst of globalization. The alpha generation, which relies on technology, shows a decline in national values. This research aims to increase the national commitment of students at SMA N 1 Mejobo Kudus through the guidance of a hybrid group with cognitive restructuring techniques. The research method uses a pre-experimental design of one group pretest-posttest with data collection through interviews, observations, and scales. The results of the wilcoxon signed rank test showed a significant increase in the average score of national commitment from 131.375 (low category) to 254.125 (very high category), with a probability value of 0.012. This increase of 122.75% shows that hybrid group guidance services with cognitive restructuring techniques are effective in strengthening national commitment. This approach has been proven to help students change their mindset and build a more positive and responsible character. Therefore, subsequent researchers are advised to expand the scope of this study by involving larger groups or using more diverse approaches to test the effectiveness of these techniques in different contexts.